Training of Peer Leaders: A Strategy to Enhance Provision of Psychosocial Support to Vulnerable Learners in Schools - Nyarayi Chinyama; Octavia Sibanda; Shingirayi Chamisa; Happy Mathew Tirivangasi (International Journal of Social Sciences & Educational Studies, 2021)
The main aim of this paper was to investigate the factors affecting the effectiveness of peer leadership training offered to peer leaders to enhance the provision of psychosocial support to vulnerable learners in schools in Amathole West Education District, South Africa. The previous research in other countries have shown that many of these training programmes lacks institutional frameworks that makes it necessary for effective peer leadership training. This Training in peer leadership programmes in schools is noteworthy. A qualitative approach and a case study research design was used to investigate the effectiveness of the orientation training given to peer leaders in schools. Semi-structured interviews were used as the main data collection tools. Four secondary schools were purposively selected. A sample size of 26 participants comprising of 4 LO teachers, 4 School Principals, 16 peer leaders, 1 District Official and 1 Learner Support Agent was used. Data was analysed using a thematic approach. The major findings revealed that the training programme for peer leaders was flawed and inadequate to cover the psychosocial support curriculum. The study concluded that the current training for peer leaders was weak and did not produce competent peer leaders. The study recommended that peer leaders should continuously be given training in different aspects of psychosocial support provision throughout the year and LSAs and LO teachers should be offered separate training as coordinators of school programmes. Lastly, peer leadership training curriculum should be reviewed to match the ongoing social transformation in schools and the programme should be allocated with a functional budget.